Selected papers from the International Scientific Conference on Numerical Heat Transfer 2005 [ - International Scientific Conference on Numerical Heat Transfer , (2005) Krakaow, Poland); Bialecki, Ryszard A.; Nowak, A. J. (Bradford, England : Emerald, 2008)
Selected papers presented during the International Scientific Conference on Numerical Heat Transfer (NHT2005). The papers demonstrate, on one hand, an overview of the conference topics and, on the other hand, to document the most important advances in numerical heat transfer.
1. Numerical simulation of complex transport phenomena arising in practical thermal systems -- 2. Verification of a numerical model of macrosegregation in direct chill casting; Finite element modelling of the squeeze casting process -- 3. Numerical analysis and experimental validation of the free surface flow and heat transfer in electrical transformers moulding processes -- 4. Thermocapillary convection and phase change in welding; Temperature in a disk brake, simulation and experimental verification
Title from PDFcover (viewed Aug 12, 2008)
Includes bibliographical references
Keywords: Heat -- Transmission -- Mathematical models -- Congresses; Numerical analysis -- Congresses